2015
DOI: 10.1111/jnc.13127
|View full text |Cite
|
Sign up to set email alerts
|

p35 and Rac1 underlie the neuroprotection and cognitive improvement induced by CDK5 silencing

Abstract: CDK5 plays an important role in neurotransmission and synaptic plasticity in the normal function of the adult brain, and dysregulation can lead to Tau hyperphosphorylation and cognitive impairment. In a previous study, we demonstrated that RNAi knock down of CDK5 reduced the formation of neurofibrillary tangles and prevented neuronal loss in triple transgenic Alzheimer’s mice. Here, we report that CDK5 RNAi protected against glutamate-mediated excitotoxicity using primary hippocampal neurons transduced with AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 85 publications
(105 reference statements)
1
22
0
2
Order By: Relevance
“…CDK5 shRNAmiR induced Rac1 activation, and the subsequent lamellipodia formation was associated with BDNF release in astrocytes and induced the astrocytic neuroprotection. Various studies, most of which have utilized neurodegenerative models, have demonstrated that CDK5 suppression or inhibition favors cell viability in the presence of an insult, as ischemia, excitotoxicity and protein aggregation (Liu et al, 2003;Menn et al, 2010;Posada-Duque et al, 2015;Putkonen et al, 2011;Slevin and Krupinski, 2009;Zheng et al, 2005) Astrocytes provide trophic and metabolic support for neuronal development, maintenance of synaptic function, and neuronal survival (Allen, 2013;Parpura and Verkhratsky, 2012;Sofroniew, 2005). These results show that glutamate exerts a negative effect on cell viability and the morphology of C6 astrocyte-type cells.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…CDK5 shRNAmiR induced Rac1 activation, and the subsequent lamellipodia formation was associated with BDNF release in astrocytes and induced the astrocytic neuroprotection. Various studies, most of which have utilized neurodegenerative models, have demonstrated that CDK5 suppression or inhibition favors cell viability in the presence of an insult, as ischemia, excitotoxicity and protein aggregation (Liu et al, 2003;Menn et al, 2010;Posada-Duque et al, 2015;Putkonen et al, 2011;Slevin and Krupinski, 2009;Zheng et al, 2005) Astrocytes provide trophic and metabolic support for neuronal development, maintenance of synaptic function, and neuronal survival (Allen, 2013;Parpura and Verkhratsky, 2012;Sofroniew, 2005). These results show that glutamate exerts a negative effect on cell viability and the morphology of C6 astrocyte-type cells.…”
Section: Discussionmentioning
confidence: 80%
“…These functions include providing metabolic and structural support to neurons and synapses, regulating excess potassium, sodium, and neurotransmitters in the synaptic cleft (Sofroniew and Vinters, 2010) and making contact with the vasculature via their end-feet to generate a protective layer that contributes to the integrity of the blood-brain barrier (BBB) (Koehler et al, 2009;Posada-Duque et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Adicionalmente, modelos in vivo indican que, el aumento sostenido de la actividad de CDK5 en la AD se correlaciona con la hiperfosforilación aberrante de la proteína Tau, formando agregados de esta proteína en el soma (Piedrahita, et al, 2010) y, por consiguiente, la inducción de muerte celular, pérdida de habilidades de aprendizaje y memoria (Posada-Duque, et al, 2015). Se ha demostrado que ratones que sobre-expresan p25 durante largos períodos de tiempo, sufren deterioro de la LTP en el hipocampo y déficits de memoria, junto con una significativa pérdida neuronal.…”
Section: Terapia Génica En Infarto Cerebral Ventajas Y Limitacionesunclassified
“…Eventos que fueron responsables de la protección de neuronas expuestas a la excitotoxicidad por glutamato y en co-cultivo con los astrocitos-CDK5 "knock-down" (KD). De interés, la inhibición de Rac1 en astrocitos bloqueó el aumento del BDNF y la neuroprotección (Posada-Duque, et al, 2015). Así el remodelamiento del citoesqueleto de actina en el estrellamiento de los astrocitos, sugiere un fenotipo funcional para la liberación de BDNF, el cual promueve la neuroprotección.…”
Section: Terapia Génica En Infarto Cerebral Ventajas Y Limitacionesunclassified
“…Interestingly, silenced BACE1 (main enzyme involved in the production of βA), in the hippocampus using adenoassociated viral vectors reduces the hyperphosphorilation of tau (Piedrahita et al, 2016) and improve cognitive function at 6 months and 12 months post-treatment, presenting a balanced phospholipid composition, by the reduction of saturated fatty acid (stearic acid (18:0), palmitic acid (16:0)) and increase of poli-unsaturated fatty acid (docosahexaenoic acid, DHA (22:6)), which prevented the activation of pro-inflammatory signaling cPLA2/AA/COX2 in old AD mice to long-term post-therapy (Villamil-Ortiz et al, 2016). Also, the silencing of CDK5 in the CA1 hippocampal area prevents the spreading of excitoxicity to other areas of the neuronal circuit (Piedrahita et al, 2010; Castro-Alvarez et al, 2014, 2015; Posada-Duque et al, 2015a) also reversing (Piedrahita et al, 2010) or preventing neurodegeneration by reduction of paired helicoidal formations (Castro-Alvarez et al, 2014) and further, decreases the β amyloidosis production (Castro-Alvarez et al, 2015). The result could be assumed as it involves the prevention of Calpain activation by reduction of the active p25/CDK5 complex formation (Posada-Duque et al, 2015a) with a clear impact on the down-regulation of phosphorilation rate of tau (Castro-Alvarez et al, 2015), as well as regulation of phosphatases and GSK3β activity (Castro-Alvarez et al, 2015).…”
Section: Preclinical Studies and Molecular Targetsmentioning
confidence: 99%